ANALISIS PENGOLAHAN DATA PROGRAM NASIONAL PEMBERDAYAAN MASYARAKATN (PNPM) MANDIRI PADA DESA GUDANG HIRANG KECAMATAN SUNGAI TABUK KABUPATEN BANJAR - M. Rais Wathani (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2017)
This research was conducted with the intention to produce an application that can manage all data user of Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri so as to facilitate  Activity Management Unit  (UPK) in terms of transaction and reporting. Gudang Hirang’s village is one of the villages located in Sungai Tabuk subdistrict, Banjar district participating in the PNPM Mandiri. The public interest in the use of this program is enormous but not supported by good data management. User program data was only recorded manually by the officer. It is still not effective considering the number of people who use the program. Judging from the problems that exist in this research, so in this research was built an application to process data of PNPM independently in Gudang Hirang Village, Sungai Tabuk Subdistrict, Banjar District covering management of customer data (user society), loan list, transaction Payments, and financial reporting that can be used in the PNPM Mandiri Activity Management Unit.